SURFACE HARDENING OF COMPACTED SNOW IN ANTARCTICA. - Stehle,N. S.; Sherwood,G. E. (1966)
Studies were conducted in the Antarctic to increase the surface strength and wearing ability of compacted snow by rolling the snow when it had excess moisture, during periods of high temperature and solar radiation, and by melting and refreezing the surface snow using controlled absorption of solar radiation. The increase of strength in the areas rolled indicated that the addition of moisture increased the strength in the top 8 inches provided the surface was rolled more than once but probably less than 10 times. Although the excess moisture in the snow during these tests was due to weather conditions, water from an outside source during rolling should promote surface hardening; field tests to investigate the addition of water before rolling are planned for the 1966-67 antarctic summer. The controlled radiation absorption tests, which were conducted late in the summer season, showed that there were limits to the effectiveness of solar radiation absorption in promoting surface hardness. (Author)